Acoustic properties and volumetric data of liquid mixtures containing valeronitrile and esteres; effects due to temperature changes - Canzonieri, Salvador Humberto (2016)
In this work experimental data of density, ρ, and velocity of sound, u, of the binary systems of valeronitrile and methyl propanoate, and valeronitrile and ethyl propanoate, at atmospheric pressure and in a range of temperature from 278.15 K to 318.15 K were reported. From experimental information, molar volume, V(x, T), excess molar volume, VE(x, T), thermal expansion coefficient, (x, T), thermal expansion coefficient of excess, E(x,T), velocity of sound deviation, Δu(x, T), isentropic compressibility, ks(x,T) and isentropic compressibility of excess, ksE(x, T), were calculated. Each set of excess results was fitted to a polynomial equation like Redlich and Kister [1] as a function of composition and temperature, with deviations within the range of experimental error. Binary mixtures studied showed negative values of E, Δu y ksE, over the whole composition and temperature range. Also, velocity of sound was predicted with the models proposed by Nomoto [2,3], Van Dael [4] and Ernst et al. [5].